2003
DOI: 10.1017/s0967199403002375
|View full text |Cite
|
Sign up to set email alerts
|

Birth of rats following nuclear exchange at the 2-cell stage

Abstract: We report full-term development of nuclear transfer embryos following nuclear exchange at the 2-cell stage. Nuclei from 2-cell rat embryos were transferred into enucleated 2-cell embryos and developed to term after transfer to recipients (NT2). Pronuclear exchange in zygotes was used for comparison (NT1). Zygotes and 2-cell embryos were harvested from 4-week-old female Sprague-Dawley rats. Nuclear transfer was performed by transferring the pronuclei or karyoplasts into the perivitelline space of recipient embr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…Reprogramming and embryonic development can occur in animals after transfer of somatic nuclei into oocytes and zygotes in metaphase of the cell cycle, but fails after transfer during interphase [68]. Nuclear transfer into embryonic blastomeres enucleated in interphase has also been attempted, but failed to demonstrated reprogramming activities [9, 10]. In particular, no development was observed after transfer of inner cell mass nuclei into 2-cell stage embryos enucleated in interphase [10].…”
Section: Resultsmentioning
confidence: 99%
“…Reprogramming and embryonic development can occur in animals after transfer of somatic nuclei into oocytes and zygotes in metaphase of the cell cycle, but fails after transfer during interphase [68]. Nuclear transfer into embryonic blastomeres enucleated in interphase has also been attempted, but failed to demonstrated reprogramming activities [9, 10]. In particular, no development was observed after transfer of inner cell mass nuclei into 2-cell stage embryos enucleated in interphase [10].…”
Section: Resultsmentioning
confidence: 99%
“…These failures most likely are due to the tetraploid nature of the reconstructed embryos [21]. The full-term developmental potential of blastomeres has been demonstrated in mouse [22][23][24] or rat [25]; however, whether the electrofusion of blastomeres affects the full-term development is still not clear. Here, we have shown that if the polyploidy of these embryos is rectified, full-term development can be recovered, even though the transcripts present in the cytoplast of blastomeres are different from zygotes [26].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we compared the developmental abilities of rat oocytes activated by four different treatments (ethanol, electrical pulses, strontium and ionomycin), which have been reported as popular agents for oocyte activation in other species (Cuthbertson et al ., 1983; Ito et al ., 2004; Méo et al ., 2005; Jellerette et al ., 2006). We also examined the developmental abilities of oocytes collected from two different outbred types of rat, SD and Wistar, that have been widely used in studies on reproductive technologies (Roh et al ., 2003; Shinozawa et al ., 2004; Hirabayashi et al ., 2005; Ross et al ., 2006). The oocytes collected from SD rats showed a significantly higher developmental ability than those collected from Wistar rats independent of activation treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ethanol treatment is also well known as a popular regent that induces oocyte activation in mice (Cuthbertson et al ., 1983), cattle (Nagai et al ., 1987) and pigs (Yamauchi et al ., 1996). It is also known that, after the use of these stimuli, additional treatment with 6-dimethylaminopurine (6-DMAP) (Méo et al ., 2005), cycloheximide (Yamanaka et al ., 2007) or puromycin (Roh et al ., 2003) improves the development of parthenogenetic or nuclear-transferred embryos in vitro .…”
Section: Introductionmentioning
confidence: 99%